2007
DOI: 10.1111/j.1460-9568.2007.05424.x
|View full text |Cite
|
Sign up to set email alerts
|

CD40 promotion of amyloid beta production occurs via the NF‐κB pathway

Abstract: The CD40 receptor is a member of the tumor necrosis factor (TNF) super-family of trans-membrane receptors. Interaction of CD40 with its ligand CD40L mediates a broad range of immune and inflammatory responses in the periphery and in the central nervous system. Recently it has been suggested that CD40/CD40L interaction is involved in amyloid precursor protein (APP) processing and Alzheimer's disease (AD)-like pathology in transgenic mouse models of AD. We have previously shown that pharmacologically inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Interestingly, the inhibition of NF-B activation reduces A␤ secretion in vitro (20 -22), and it was suggested that this could occur by interfering with ␤APP processing (22)(23)(24)(25)(26)(27). In this context, it is noteworthy that we and others previously showed that NF-B mediated the A␤-associated increase of BACE1 transcriptional activity (28,29) but to date, there is relatively little data concerning the putative control of the ␥-secretase build-up and activity or on the expression of ␤APP by NF-B; and, if so, if this control may be dependent on A␤.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Interestingly, the inhibition of NF-B activation reduces A␤ secretion in vitro (20 -22), and it was suggested that this could occur by interfering with ␤APP processing (22)(23)(24)(25)(26)(27). In this context, it is noteworthy that we and others previously showed that NF-B mediated the A␤-associated increase of BACE1 transcriptional activity (28,29) but to date, there is relatively little data concerning the putative control of the ␥-secretase build-up and activity or on the expression of ␤APP by NF-B; and, if so, if this control may be dependent on A␤.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…A similar trend toward nonamyloidogenic processing and anti-AD protection is also observed in significantly down-regulated genes depicted in the NanoString nCounter heat map. Among them are glycogen synthase kinase 3-β (GSK3β) (−1.4-fold, P < 0.0001), Nicastrin (NCSTN) (−3.2-fold, P < 0.0001), anterior pharynx-defective 1 (APH1) (−1.8-fold, P < 0.0001), β-site APP-Cleavage Enzyme 1 (BACE1) (−1.7-fold, P < 0.0001), BACE2 (−3.2-fold, P < 0.0001), cluster of differentiation 40 ligand (CD40L) (−1.5-fold, P < 0.01), and C-X-C Motif Chemokine Receptor 2 (CXCR2) (−2.0-fold, P < 0.0001), which are all genes hypothesized to counter AD phenotype and pathogenesis ( 37 , 39 41 ). In the case of late-onset AD (LOAD) genes, apolipoprotein-E-ε4 (APOEε4) is reduced (−1.8-fold, P < 0.0001), which may be therapeutically beneficial ( 21 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the effect of flavonoids on NFκB activity since flavonoids are known to display anti-inflammatory properties [16] and since we have shown previously that compounds of unrelated structure that inhibit NFκB activation can lower Aβ production by targeting the β-cleavage of APP [17, 18]. We observed that all of the flavonoids unable to significantly lower Aβ level in whole cells for the dose range tested (PD98059, taxifolin, genistein, daidzein and baicalein) were also unable to reduce NFκB activation induced by TNF±, whereas Aβ and APPsβ lowering flavonoids (kaempferol, quercetin, acacetin, apigenin and luteolin) dose dependently inhibited NFκB activation (Figure 6).…”
Section: Resultsmentioning
confidence: 99%